Analysis and optimization for the process of glass tempering using autoclave (2018)
A mathematical analysis of the glass tempering process was carried out using an autoclave, varying the operating parameters of the system. It was found that the process time can be reduced by up to 3.23% by changing the resistance to 15Ω, but increasing the resistance more than this value would mean compromising the quality of the final product. Thus, it is advisable to make variations of the resistance between 10Ω and15Ω, which will allow the optimization of the process time and pressures without affecting the quality of the result